Expression of the postsynaptic scaffold PSD‐95 and development of synaptic physiology during giant terminal formation in the auditory brainstem of the chicken. (23rd April 2015) - Goyer, David; Fensky, Luisa; Hilverling, Anna Maria; Kurth, Stefanie; Kuenzel, Thomas
Abstract In the avian nucleus magnocellularis (NM) endbulb of Held giant synapses develop from temporary bouton terminals. The molecular regulation of this process is not well understood. Furthermore, it is unknown how the postsynaptic specialization of the endbulb synapses develops. We therefore analysed expression of the postsynaptic scaffold protein PSD‐95 during the transition from bouton‐to‐endbulb synapses. PSD‐95 has been implicated in the regulation of the strength of glutamatergic synapses and could accordingly be of functional relevance for giant synapse formation. PSD‐95 protein was expressed at synaptic sites in embryonic chicken auditory brainstem and upregulated between embryonic days (E)12 and E16. We applied immunofluorescence staining and confocal microscopy to quantify pre‐and postsynaptic protein signals during bouton‐to‐endbulb transition. Giant terminal formation progressed along the tonotopic axis in NM, but was absent in low‐frequency NM. We found a tonotopic gradient of postsynaptic PSD‐95 signals in NM. Furthermore, PSD‐95 immunosignals showed the greatest increase between E12 and E15, temporally preceding the bouton‐to‐endbulb transition. We then applied whole‐cell electrophysiology to measure synaptic currents elicited by synaptic terminals during bouton‐to‐endbulb transition. With progressing endbulb formation postsynaptic currents rose more rapidly and synapses were less susceptible to short‐term depression, but currents were not different in amplitude or decay‐time constant. We conclude that development of presynaptic specializations follows postsynaptic development and speculate that the early PSD‐95 increase could play a functional role in endbulb formation.